Stimulating Children's Numerical Literacy: The Effectiveness of Singing Favorite Food Songs - Yulsyofriend; Mafardi; Tia Novela; Vivi Anggraini; Adi Priyanto (Program Studi Magister Pendidikan Anak Usia Dini, 2023)
Numerical literacy is the ability needed to use number ideas and arithmetic skills in everyday situations as well as the ability to analyze quantitative data around children. This study aims to determine the effect of the intervention of singing favorite food songs on children's numerical literacy. Using a pretest-posttest experimental design with a control group, this study involved 20 children as research objects, consisting of 10 experimental class children and 10 control class children. The results of the study showed that singing activities with the theme of favorite food influenced the numerical literacy of kindergarten children. This singing activity attracts children's interest, thus showing a significant difference between the experimental class and the control class. Therefore, for further research, it is suggested that early childhood educators can always take advantage of artistic activities such as singing to attract children's interest in any learning. Keywords: early childhood, numerical literacy, singing activities References: Anvari, S. H., Trainor, L. J., Woodside, J., & Levy, B. A. (2002). Relations among musical skills, phonological processing, and early reading ability in preschool children. Journal of Experimental Child Psychology, 83(2), 111–130. https://doi.org/10.1016/S0022-0965(02)00124-8 Barrett, M. S. (2006). Inventing songs, inventing worlds: The ‘genesis’ of creative thought and activity in young children’s lives. International Journal of Early Years Education, 14(3), 201–220. https://doi.org/10.1080/09669760600879920 Batchelor, S., Keeble, S., & Gilmore, C. (2015). Magnitude Representations and Counting Skills in Preschool Children. Mathematical Thinking and Learning, 17(2–3), 116–135. https://doi.org/10.1080/10986065.2015.1016811 Dixon-Krauss, L., Januszka, C. M., & Chae, C.-H. (2010). Development of the Dialogic Reading Inventory of Parent-Child Book Reading. Journal of Research in Childhood Education, 24(3), 266–277. https://doi.org/10.1080/02568543.2010.487412 Duncan, G. J., Dowsett, C. J., Claessens, A., Magnuson, K., Huston, A. C., Klebanov, P., Pagani, L. S., Feinstein, L., Engel, M., Brooks-Gunn, J., Sexton, H., Duckworth, K., & Japel, C. (2007). School readiness and later achievement. Developmental Psychology, 43(6), 1428–1446. https://doi.org/10.1037/0012-1649.43.6.1428 Goldstein, H. (2011). Knowing What to Teach Provides a Roadmap for Early Literacy Intervention. Journal of Early Intervention, 33(4), 268–280. https://doi.org/10.1177/1053815111429464 Haimson, J., Swain, D., & Winner, E. (2011). Do Mathematicians Have Above Average Musical Skill? Music Perception, 29(2), 203–213. https://doi.org/10.1525/mp.2011.29.2.203 Harrison, C. S. (1996). Relationships between Grades in Music Theory for Nonmusic Majors and Selected Background Variables. Journal of Research in Music Education, 44(4), 341–352. https://doi.org/10.2307/3345446 Helmrich, B. H. (2010). Window of Opportunity? Adolescence, Music, and Algebra. Journal of Adolescent Research, 25(4), 557–577. https://doi.org/10.1177/0743558410366594 Howse, R. B., Lange, G., Farran, D. C., & Boyles, C. D. (2003). Motivation and Self-Regulation as Predictors of Achievement in Economically Disadvantaged Young Children. The Journal of Experimental Education, 71(2), 151–174. https://doi.org/10.1080/00220970309602061 Jones, M. R., & Bergee, M. (2008). Elements Associated with Success in the First-Year Music Theory and Aural-Skills Curriculum. Journal of Music Theory Pedagogy, 22. Kleemans, T., Peeters, M., Segers, E., & Verhoeven, L. (2012). Child and home predictors of early numeracy skills in kindergarten. Early Childhood Research Quarterly, 27(3), 471–477. https://doi.org/10.1016/j.ecresq.2011.12.004 Lessard, A., & Bolduc, J. (2011). Links between Musical Learning and Reading for First to Third Grade Students: A Literature Review. International Journal of Humanities and Social Science, 1(7). Lyons, I. M., & Ansari, D. (2015). Numerical Order Processing in Children: From Reversing the Distance-Effect to Predicting Arithmetic. Mind, Brain, and Education, 9(4), 207–221. https://doi.org/10.1111/mbe.12094 Lyons, I. M., Price, G. R., Vaessen, A., Blomert, L., & Ansari, D. (2014). Numerical predictors of arithmetic success in grades 1–6. Developmental Science, 17(5), 714–726. https://doi.org/10.1111/desc.12152 Manolitsis, G., Georgiou, G. K., & Tziraki, N. (2013). Examining the effects of home literacy and numeracy environment on early reading and math acquisition. Early Childhood Research Quarterly, 28(4), 692–703. https://doi.org/10.1016/j.ecresq.2013.05.004 Mehr, S. A., Schachner, A., Katz, R. C., & Spelke, E. S. (2013). Two Randomized Trials Provide No Consistent Evidence for Nonmusical Cognitive Benefits of Brief Preschool Music Enrichment. PLoS ONE, 8(12), e82007. https://doi.org/10.1371/journal.pone.0082007 Mol, S. E., & Neuman, S. B. (2014). Sharing information books with kindergartners: The role of parents’ extra-textual talk and socioeconomic status. Early Childhood Research Quarterly, 29(4), 399–410. https://doi.org/10.1016/j.ecresq.2014.04.001 Mundy, E., & Gilmore, C. K. (2009). Children’s mapping between symbolic and nonsymbolic representations of number. Special Issue: Typical Development of Numerical Cognition, 103(4), 490–502. https://doi.org/10.1016/j.jecp.2009.02.003 Neuman, S. B., Kaefer, T., & Pinkham, A. M. (2018). A Double Dose of Disadvantage: Language Experiences for Low-Income Children in Home and School. Journal of Educational Psychology, 110(1), 102–118. https://doi.org/10.1037/edu0000201 Pekrun, R. (2006). The Control-Value Theory of Achievement Emotions: Assumptions, Corollaries, and Implications for Educational Research and Practice. Educational Psychology Review, 18(4), 315–341. https://doi.org/10.1007/s10648-006-9029-9 Peng, P., Namkung, J., Barnes, M., & Sun, C. (2016). A meta-analysis of mathematics and working memory: Moderating effects of working memory domain, type of mathematics skill, and sample characteristics. Journal of Educational Psychology, 108(4), 455–473. https://doi.org/10.1037/edu0000079 Protzko, J. (2017). Raising IQ among school-aged children: Five meta-analyses and a review of randomized controlled trials. Developmental Review, 46, 81–101. https://doi.org/10.1016/j.dr.2017.05.001 Purpura, D. J., Hume, L. E., Sims, D. M., & Lonigan, C. J. (2011). Early literacy and early numeracy: The value of including early literacy skills in the prediction of numeracy development. Journal of Experimental Child Psychology, 110(4), 647–658. https://doi.org/10.1016/j.jecp.2011.07.004 Rauscher, F., Shaw, G., Levine, L., Wright, E., Dennis, W., & Newcomb, R. (1997). Music training causes long-term enhancement of preschool children’s spatial–temporal reasoning. Neurological Research, 19(1), 2–8. https://doi.org/10.1080/01616412.1997.11740765 Rohwer, D. (2012). Predicting Undergraduate Music Education Majors’ Collegiate Achievement. Texas Music Education Research. Santos-Luiz, C. dos. (2007). The learning of music as a means to improve mathematical skills. Sarnecka, B. W., & Wright, C. E. (2013). The Idea of an Exact Number: Children’s Understanding of Cardinality and Equinumerosity. Cognitive Science, 37(8), 1493–1506. https://doi.org/10.1111/cogs.12043 Singh, N. (2016). Mathematics and Music. INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH, 5(10). https://doi.org/DOI: 10.36106/ijsr Slusser, E. B., & Sarnecka, B. W. (2011). Find the picture of eight turtles: A link between children’s counting and their knowledge of number word semantics. Journal of Experimental Child Psychology, 110(1), 38–51. https://doi.org/10.1016/j.jecp.2011.03.006 Taylor, S. V., & Leung, C. B. (2020). Multimodal Literacy and Social Interaction: Young Children’s Literacy Learning. Early Childhood Education Journal, 48(1), 1–10. https://doi.org/10.1007/s10643-019-00974-0 Vaiouli, P., & Friesen, A. (2016). The Magic of Music: Engaging Young Children with Autism Spectrum Disorders in Early Literacy Activities With Their Peers. Childhood Education, 92(2), 126–133. https://doi.org/10.1080/00094056.2016.1150745 Vaiouli, P., & Ogle, L. (2015). Music Strategies to Promote Engagement and Academic Growth of Young Children with ASD in the Inclusive Classroom. Young Exceptional Children, 18(2), 19–28. https://doi.org/10.1177/1096250614523968 Vaughn, K. (2000). Music and Mathematics: Modest Support for the Oft-Claimed Relationship. Journal of Aesthetic Education, 34(3/4), 149–166. JSTOR. https://doi.org/10.2307/3333641 Wagner, J. B., & Johnson, S. C. (2011). An association between understanding cardinality and analog magnitude representations in preschoolers. Cognition, 119(1), 10–22. https://doi.org/10.1016/j.cognition.2010.11.014 Whitehurst, G. J., & Lonigan, C. J. (1998). Child Development and Emergent Literacy. Child Development, 69(3), 848–872. https://doi.org/10.1111/j.1467-8624.1998.tb06247.x Wynn, K. (1990). Children’s understanding of counting. Cognition, 36(2), 155–193. https://doi.org/10.1016/0010-0277(90)90003-3